2017
DOI: 10.1186/s12875-017-0613-5
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of primary care models for non-communicable disease interventions in Sub-Saharan Africa

Abstract: BackgroundChronic diseases, primarily cardiovascular disease, respiratory disease, diabetes and cancer, are the leading cause of death and disability worldwide. In sub-Saharan Africa (SSA), where communicable disease prevalence still outweighs that of non-communicable disease (NCDs), rates of NCDs are rapidly rising and evidence for primary healthcare approaches for these emerging NCDs is needed.MethodsA systematic review and evidence synthesis of primary care approaches for chronic disease in SSA. Quantitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
113
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(119 citation statements)
references
References 40 publications
(152 reference statements)
4
113
0
2
Order By: Relevance
“…Similarly, self‐measurement of blood pressure is rarely done, and blood pressure is not measured at each clinic. Limited time and space in clinics, or low awareness or lack of training among health professionals may contribute to the poor ‘cascade of care’ in DM care in low‐resource settings .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, self‐measurement of blood pressure is rarely done, and blood pressure is not measured at each clinic. Limited time and space in clinics, or low awareness or lack of training among health professionals may contribute to the poor ‘cascade of care’ in DM care in low‐resource settings .…”
Section: Discussionmentioning
confidence: 99%
“…Primary care is for most patients the gateway to the healthcare system, yet in resource-limited settings, most primary healthcare is focused on acute episodic care and chronic disease is often deferred to specialist care delivered at secondary and tertiary centres. 15 The findings of the study call for improvement and greater investment in the prevention and control of NCDs, in particular T2DM, by primary health institutions in Qatar. It must also be noted that appropriately qualified and trained public health professionals to have the appropriate expertise and skills to take the responsibility of planning and providing preventive interventions for NCD patients.…”
Section: Bmj Nutrition Prevention and Healthmentioning
confidence: 96%
“…Numbers of studies have shown that cardiovascular disease became the most common chronic disease with the progress of society and changes of people's life, which was an important burden of global public health in most countries [20][21][22]. Accumulating evidences suggested that endothelial dysfunction was one of the critical determinants in pathogenesis of atherosclerotic cardiovascular disease, and angiocardiopathy such as myocardial infarction, stroke, and vascular remodeling was independently associated with endothelial dysfunction [23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%